Vertical Head Movements Influence Memory Performance for Words With Emotional Content - Globig, Laura K.; Hartmann, Matthias; Martarelli, Corinna S. (Frontiers in Psychology, 2019)
Numerous studies have found an association between valence and the vertical dimension of space (good-up, bad-down). This association has also been linked to sensorimotor experiences (e.g., body movements). In this study we investigated whether body movements along the vertical plane play an active role in the retrieval of positive and negative words (as well as words with a more explicit association with up and down). Twenty-five participants were presented with a list of nouns associated with space (e.g., satellite, underground) and a list of nouns associated with emotions (e.g., joy, war). Subsequently, they had to retrieve the words while performing vertical head movements. We found a vertical effect in that participants retrieved more positive words when moving their head upwards and more negative words when moving the head downwards. These results illustrate that overt body movements are indeed associated with emotional information and can thereby influence what we remember. We conclude that abstract concepts such as emotional representations are inherently linked to motor action and are grounded in space.